Oral miltefosine for Indian post‐kala‐azar dermal leishmaniasis: a randomised trial. Issue 1 (8th November 2012) - Sundar, Shyam; Sinha, Prabat; Jha, T. K.; Chakravarty, Jaya; Rai, Madhukar; Kumar, Nawin; Pandey, Krishna; Narain, M. K.; Verma, N.; Das, V. N. R.; Das, P.; Berman, Jonathan; et al.
Abstract Objective Standard treatment of Indian post‐kala‐azar dermal leishmaniasis (PKDL) is unsatisfactory because to achieve therapeutic effectiveness, heroic courses of parenteral and toxic agents have to be administered. Our objective was to evaluate oral miltefosine for its potential to provide effective as well as tolerable treatment for this disease. Method Open‐label, randomised, parallel‐group multicentric trial. Miltefosine, 100 mg/day to all but one patient, was administered for 12 weeks or 8 weeks, with a target of 18 patients in each treatment group. Key endpoints were tolerance during treatment and efficacy at 12 months of follow‐up. Results The ITT and per‐protocol cure rates after 12 months of follow‐up for patients receiving 12 weeks of therapy were 78% (14 of 18 patients: 95% CI = 61–88%) and 93% (14 of 15 patients: 95% CI = 71–95%), respectively, after 12 months of follow‐up. The ITT and per‐protocol cure rates for patients receiving 8 weeks of therapy were 76% (13 of 17 patients: 95% CI = 53–90%) and 81% (13 of 16 patients: 95% CI = 57–93%), respectively. Gastrointestinal and other adverse events were rare. Conclusions This study suggests that oral miltefosine for 2–3 months can be considered a treatment of choice for Indian PKDL.